Experimental analysis of clay bricks incorporated with phase change material for enhanced thermal energy storage in buildings. (1st August 2023) - Gupta, Manglesh Kumar; Rathore, Pushpendra Kumar Singh; Kumar, Rajan; Gupta, Naveen Kumar
Abstract: This study analyses the effect on thermal performance of clay bricks integrated with two different PCM using macrocapsules of different shapes. Tubular shape, square shape, and rectangular shape of macrocapsules were used to integrate PCM loaded with 20 wt% graphite and without graphite in the bricks. Thermal behaviour of all the bricks was investigated under real tropical environment for three consecutive days. Various parameters such as peak temperature, thermal amplitude, time lag, decrement factor, and heat transfer rate were investigated. Additionally, reduction in cooling load and corresponding cost savings in energy was also evaluated. Peak temperature reduction from maximum 9.87 % to minimum 1.81 % was observed in all the PCM bricks in comparison to conventional brick. Tubular encapsulated PCM brick without graphite has shown maximum reduction of 33.33 % and 33.20 % for day 1 and day 2 in thermal amplitude followed by square encapsulated PCM brick without graphite of 27.43 % for day 3. A maximum cooling load reduction of 23.66 % was observed in tubular shape encapsulated bricks without graphite and minimum cooling load reduction of 3.31 % was observed in rectangular shape encapsulated brick with graphite in comparison with conventional brick. Highlights: Clay bricks were incorporated with different shapes of macroencapsulated PCM. Macrocapsules contain n-octadecane and capric acid loaded with and without graphite. Peak temperature reduction ranging from 4.20 °C to 0.77 °C was obtained. Maximum cooling load reduction of 23.66 % was obtained by tubular shape macrocapsule brick.